(untitled) (Eurasian Journal of Ecology, 2016)
On the homeostasis or internal environment of researchers holding on this issue before sihpor no consensus. In data time the concept of " internal environment " in the scientific literature on the biology, medicine is fully engaged. For example there is the concept of " external environment" – is the environment around us , in other ecological environment where we live , and the " internal environment " of its elements . Therefore, there is a constant between these, durable bond, where share their border epithelial membranes. Therefore, different specialists , anatomy, morphology , philosophy and psychology provide " internal environment" different definitions.